Cytokine profiles and the relationship of disease severity in patients with psoriasis - Qingqing Wang; Dong Yan; Shuting Zheng; Min Li; Jialin Li; Xiuyu Fu; Dandan Fu; Hua Hu; Xiangfeng Song; Zhongwei Tian (Wolters Kluwer Medknow Publications, 2022)
Background: Psoriasis is a chronic skin disease characterized by hyperproliferation of keratinocytes and increased inflammation. Previous studies have detected the levels of cytokines in the serum of patients with psoriasis, yet few multi-cytokine combination studies have been reported. Objective: The aim of the study was to compare the levels of cytokines in the serum between patients with psoriasis and healthy controls, elucidate which factors influence the psoriasis progression. Methods: A total of 39 psoriasis patients and 30 healthy volunteers were enrolled. The venous blood was collected and the levels of 13 inflammatory cytokines were measured by human inflammation panel 1 kit. The severity of the disease was determined according to the psoriasis area and severity index (PASI) score. Results: Compared with healthy controls, the levels of nine cytokines (IFN-γ, TNF-α, IL-1β, IL-6, IL-10, IL-12P40, IL-18, IL-17A and IL-23) were significantly increased, while the level of MCP-1 decreased in psoriatic patients. In addition, except for MCP-1, IL-10 and IL-12P40, these cytokine levels were positively correlated with the PASI score. Furthermore, there were higher serum lever of IFN-γ, TNF-α, IL-1β, IL-6, IL-17A, IL-18 and IL-23 in active psoriasis than healthy controls and retrograde psoriasis. Conclusions: Increased serum levels of IFN-γ, TNF-α, IL-1β, IL-6, IL-17A, IL-18 and IL-23 in psoriatic patients were associated with PASI and the stage of disease, which suggested that these cytokines play an important role in the pathogenesis of psoriasis. The detection of these cytokines can better observe the disease activity of psoriasis and optimize the treatment strategy.